FOSTERING COMMUNICATIVE COMPETENCE THROUGH STRUCTURED PEER EVALUATION: A SOCIOCULTURAL STUDY AMONG ENGINEERING STUDENTS - Shah, Nur Shaqira Adera Mohd; Zuki, Nor Syafawati Mohd; Mahmood, Muhammad Bazli; Dziauddin, Sharifah Anis Zarith Syed; Hakimi, Nur Adila (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study examines the impact of rubric-based peer feedback on language learning among Diploma in Engineering students at Universiti Malaysia Perlis (UniMAP), grounded within Vygotsky’s Sociocultural Theory. Peer evaluations among students were often hindered by reluctance to provide meaningful commentary, typically resulting in vague, one-word responses such as "good" or "okay." These superficial comments reflected a fear of offending peers rather than an assessment of speaking performance. Drawing from the principles of scaffolding and the Zone of Proximal Development (ZPD), this study introduced a structured rubric to guide students in delivering respectful, detailed, and academically appropriate feedback. A quantitative survey comprising 20 Likert-scale items was administered to 74 engineering students following rubric-based peer feedback sessions. Descriptive statistical analysis revealed highly positive perceptions: 91.9% of participants agreed that rubric use enhanced their understanding of speaking skills, self-awareness, and confidence. The structured rubric functioned as an effective scaffold, promoting higher-order thinking, self-regulation, and critical reflection. These findings support the theoretical framework suggesting that rubrics scaffold evaluative processes, minimize social anxiety, and promote targeted language development through social interaction. By fostering meaningful peer interaction, rubric-guided feedback activities align with sociocultural learning paradigms and highlight the importance of structured peer interventions in technical education contexts where language proficiency and respectful academic discourse are essential. Implications for practice and future research directions are discussed.